PENGARUH PROFESIONALISME KERJA APARAT TERHADAP KUALIAS PELAYANAN PUBLIK DI KANTOR DESA ANABANNAE KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Erni Nawir; Monalisa Ibrahim; Hariyanti Hamid (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
The aim of this research is to find out the influence of the professionalism of the apparatus work towards the quality of public services in the Anabannae Village office, Pitu Riawa District, Sidenreng Rappang Regency. The population of this study was 1,181 people and a sample of 92 people. The sampling technique used is random sampling. This type of research is quantitative descriptive. Data collection techniques are observation, interviews, library research and questionnaires. Data analysis techniques using descriptive analysis, data quality tests (validity and reliability), classic assumption tests, linear regression and hypothesis testing and with the help of SPSS version 21 application. The results showed that the professionalism of the work apparatus 59.6% was not good. the quality of public service 59.16% is not good. Factors that influenced the professionalism of work 60.32% were unfavorable including 31.4% proficiency, 58.6% readiness, 60% responsibility, 61.2% discipline, and 60.4% employee attitude. This shows the Effect of Professional Workers' Apparatuses on the Quality of Public Services at the Anabannae Village Office in Pitu Riawa Subdistrict is 59% of the 100% expected results, which are classified as